How COVID-19 may disrupt food supply chains in developing countries - Reardon, Thomas; Bellemare, Marc F.; Zilberman, David (International Food Policy Research Institute, 2020)
COVID-19 is spreading through the developing world. Many low- and middle-income countries are now reporting growing numbers of cases and imposing rigorous lockdown regulations in response, which impact all aspects of the economy. How will COVID-19 affect food-supply chains (FSCs) in developing countries? The evidence suggests that the impacts will be felt widely, but unevenly. Farm operations may be spared the worst, while small and medium-sized enterprises (SMEs) in urban areas will face significant problems. Governments will have to develop policies to respond to these varied impacts to avoid supply chain disruptions, higher food prices, and severe economic fallout for millions of employees.